Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories - Shavrin, Alexey V. (Zootaxa, 2014)
The type and additional material from adjacent territories of species of the genus Lesteva Latreille, 1797 of Iran are revised. Eight species are recognized, three of which are described as new: L. (s.str.) frischi sp.n. (Iran, Esfahan), L. (s.str.) schawalleri sp.n. (Iran, Elburs) and L. (s.str.) antennata sp.n. (Iran, Golestan). Two synonyms are proposed: L. (s.str.) binotata Reitter, 1901 = L. (s.str.) syriaca Luze, 1903, syn. n., L. (s.str.) longoelytrata longoelytrata (Goeze, 1777) = L. (s.str.) soror Smetana, 1967, syn. n. A key to species known from Iran and new provincial records for L. (s.str.) binotata Reitter, L. (s.str.) longoelytrata longoelytrata (Goeze), L. (s.str.) maculipennis Luze, 1903 and L. (Lestevidia) punctata Erichson, 1839 are provided. L. (s.str.) binotata Reitter and L. (s.str.) maculipennis are redescribed. Aedeagi of all new species, L. (s.str.) binotata, L. (s.str.) longoelytrata longoelytrata and L. (s.str.) maculipennis, as well as the antennae of all species and the variability of elytral maculae for two redescribed species  are illustrated.